2019
DOI: 10.21203/rs.2.10697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison between the Disposcope endoscope and fiberoptic bronchoscope for nasotracheal intubation-A randomized controlled trial

Abstract: Background Nasotracheal intubation (NTI) is frequently performed in oral and maxillofacial surgeries. This study evaluated whether NTI is easier when guided by Disposcope endoscopy or fiberoptic bronchoscopy. Methods Sixty patients (30 per group) requiring NTI were randomly assigned to undergo fiberoptic bronchoscopy-guided (fibreoptic group) or Disposcope endoscope-guided (Disposcope group) NTI. Then, the NTI time were recorded. Epistaxis was recorded using direct laryngoscopy five minutes after completing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Thermosoftening of the endotracheal tube should not be overlooked even if other effective methods, such as telescoping the endotracheal tube into a rubber catheter, have already been applied because it has the obvious advantages of reducing the incidence of epistaxis and improving the nasal passage of the endotracheal tube [3,15]. The wire-reinforced tracheal tube in our study is a soft endotracheal tube that contributes to reducing bleeding [9]. Therefore, simple thermosoftening treatment of the endotracheal tube has not been performed in the present research.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Thermosoftening of the endotracheal tube should not be overlooked even if other effective methods, such as telescoping the endotracheal tube into a rubber catheter, have already been applied because it has the obvious advantages of reducing the incidence of epistaxis and improving the nasal passage of the endotracheal tube [3,15]. The wire-reinforced tracheal tube in our study is a soft endotracheal tube that contributes to reducing bleeding [9]. Therefore, simple thermosoftening treatment of the endotracheal tube has not been performed in the present research.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that the wire tube body of the Disposcope endoscope was rigid but could be bent along the radian of the nasal cavity, which bene tted NTI [9]. Another device, a video intubating stylet for NTI, which has a rigid intubating stylet with an adjustable distal portion, makes the process of NTI quicker and easier [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft tracheal tubes, such as reinforced tubes, tend to move along the posterior pharyngeal wall rather than towards the laryngeal inlet, and they are di cult to navigate to the vocal cords without using Magill forceps [8]. A rigid wire tube body of a video stylet bent along the curve of the nasal cavity was reported to help anaesthesiologists complete NTI more easily [9]. However, not all institutions have visual devices.…”
Section: Introductionmentioning
confidence: 99%